2014
DOI: 10.1007/978-3-319-11280-0_5
|View full text |Cite|
|
Sign up to set email alerts
|

Membrane Rafts in the Erythrocyte Membrane: A Novel Role of MPP1p55

Abstract: Abbreviations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 98 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…in [ 21 ]). Our recent studies demonstrated that a peripheral membrane protein, MPP1/p55 (membrane palmitoylated protein 1), takes part in the regulation of PM lateral organization of erythrocyte precursors (reviewed in [ 22 ]). MPP1, a MAGUK (membrane associated guanylate kinases) family protein, was originally described in erythrocytes as a skeletal protein that participates in the linking of the membrane skeleton elements to the PM by formation of a tripartite complex with protein 4.1 and glycophorin C [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…in [ 21 ]). Our recent studies demonstrated that a peripheral membrane protein, MPP1/p55 (membrane palmitoylated protein 1), takes part in the regulation of PM lateral organization of erythrocyte precursors (reviewed in [ 22 ]). MPP1, a MAGUK (membrane associated guanylate kinases) family protein, was originally described in erythrocytes as a skeletal protein that participates in the linking of the membrane skeleton elements to the PM by formation of a tripartite complex with protein 4.1 and glycophorin C [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite several years of research, there is no great progress towards answering this question. For example, as was mentioned previously [4] there have been several raft-dependent signaling pathways found in red blood cells, e.g. Gsa-protein coupled b-adrenergic receptors cAMP-kinase A leading to the phosphorylation of adducin [5,6].…”
Section: Introductionmentioning
confidence: 83%
“…The functional role of MPP1 palmitoylation is currently not well understood but it is believed that MPP1 palmitoylation is a crucial event involved in raft formation, which might be linked to pathology [4,28,61]. Studies performed on erythroid precursor cell line HEL cells revealed that following inhibition of palmitoylation by treatment with the potent protein acetyltransferase (PAT) inhibitor 2-BrP (2-bromo palmitate), the amount of DRM fraction was markedly decreased.…”
Section: Mpp1 Is Involved In Resting State Raft Formation In Erythroimentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of the structure of such domains by cholesterol depletion may lead to modification of signal transduction. We hypothesize that simvastatin may specifically disorganize membrane rafts and therefore disturb the EGFR-dependent signalling pathways which usually promote cell proliferation and metastasis in epithelial cancers [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%